2020
DOI: 10.1159/000512041
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Male Breast Lesions According to the IAC Yokohama System for Reporting Breast Cytopathology

Abstract: <b><i>Objective:</i></b> This study aims to determine the diagnostic utility of the International Academy of Cytology (IAC) Yokohama System for reporting breast cytopathology in lesions of the male breast. <b><i>Study Design:</i></b> Fine-needle aspiration biopsy (FNAB) reports between 2015 and 2019 were retrospectively recategorized according to the 5-tiered IAC Yokohama Reporting System. Our database yielded a total of 1,532 FNAB reports from breast lesions, ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 12 publications
3
10
0
1
Order By: Relevance
“…The IAC Yokohama System has defined minimum criteria for adequacy and recommends the inadequate rates (category I) be less than 5%. Category I in published studies ranges from 5.7% to 40% 9‐14 . Our study reports a higher percentage of inadequate aspirates (9%) than that recommended by IAC, despite being comparable to other recently published Indian and Western studies 9‐14 …”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The IAC Yokohama System has defined minimum criteria for adequacy and recommends the inadequate rates (category I) be less than 5%. Category I in published studies ranges from 5.7% to 40% 9‐14 . Our study reports a higher percentage of inadequate aspirates (9%) than that recommended by IAC, despite being comparable to other recently published Indian and Western studies 9‐14 …”
Section: Discussionsupporting
confidence: 82%
“…Category I in published studies ranges from 5.7% to 40% 9‐14 . Our study reports a higher percentage of inadequate aspirates (9%) than that recommended by IAC, despite being comparable to other recently published Indian and Western studies 9‐14 …”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…La citología puede ser utilizada para un diagnóstico preliminar en la evaluación de la mayoría de las lesiones mamarias palpables clínicamente o de aquellas impalpables detectadas por imagenología, de carácter benigno y maligno, tanto en pacientes femeninos como masculinos. El riesgo de malignidad para cada categoría, resumido aquí de estudios recientes, es como sigue: para la categoría Inadecuada/insuficiente hasta 11%; Benigna de 3% a 8,3%; Atípica de 17% a 28%; Sospechosa para malignidad de 56% a 78,8% y para la categoría Maligna entre 98,8% a 100%; observándose claramente que va aumentando, a medida que aumenta la severidad de las alteraciones cito-morfológicas [3][4][5][6].…”
Section: Introductionunclassified
“…Oosthuizen et al 19 showed that the IAC system could be used to classify male breast tumors in a 5-year series of 1532 male breast FNAB cases, which yielded case distributions and ROM of 40% and 11% for the inadequate category, 57% and 3% for the benign category, 0.6% and 28% for the atypical category, 0.7% and 56% for the suspicious for malignancy category, and 1.6% and 100% for the malignant category. The sensitivity, specificity, PPV, and NPV were 63%, 100%, 100%, and 84.6%, respectively, when only malignant surgical pathology was considered positive.…”
mentioning
confidence: 99%